Challenges faced by estate school students in online education during the COVID -19 pandemic - Alagaraja, R.; Dushanthy Jeney, C. (University of Jaffna, 2022)
Education is one of the most fundamental human activities and is an essential social institution. Durkheims viewpoints of education as the socialization of the next generation. The COVID-19 pandemic has an impact on all aspects of society as a biological disaster, and it has a global impact on education. The traditional face-to-face teaching classroom system was replaced with an online system to protect the students from COVID-19 infections. This study aims to explore the challenges faced by estate school students during online education. The study was carried out using a qualitative research method in lower Cranley estate which is located in Nuwaraeliya district of Sri Lanka. Total of 30 people selected through a purposive sampling method, including 20 students, 5 parents, and 5 teachers. Primary data were gathered through 10 case studies, 20 interviews, and field observation. The thematic method was used to obtain the results. Students from working-class backgrounds do not have adequate economic, infrastructure, and study facilities to study on an online platform. In the online study system, they faced numerous social and psychological challenges and issues, including frustration, anger, anxiety, low self-esteem, lack of interest in education, and school dropouts. The cultural habits, social, and cultural capital of working-class communities have a detrimental impact on their children’s education. Therefore, online education is increasing social reproduction in society. Poor people were unable to access the online education. It has provided numerous benefits to people in the middle and upper classes. It will have an impact on the future educational achievement of the community, so there is a strong need to ensure free educational rights in Sri Lanka. Government and non-governmental organizations are needed to work on poor working-class children’s education during the COVID-19 pandemic because it affects not only their education but also their social mobility.
Keywords: COVID-19; Culture capital; Education; Pandemic; Estate